Normative values in healthy adults for the 6-minute and 2-minute walk tests in Belgium and Vietnam: implications for clinical practice - Duy Thanh Nguyen; Massimo Penta; Claire Questienne; Johanne Garbusinski; Chinh Van Nguyen; Chloé Sauvage (Medical Journals Sweden, 2024)
Objective: To establish reference values for the 6-minute walk test (6MWT) and 2-minute walk test (2MWT) distances, to investigate the correlation between these 2 tests, and to establish prediction equations for these distances in healthy populations of Belgium and Vietnam. Design: Cross-sectional study. Subjects and methods: The 6MWT and 2MWT were administered to a convenience sample of 239 Belgian and 303 Vietnamese participants between the ages of 18 and 80 years. Results: The mean (standard deviation; SD) 2MWT distances were 215 (32.8) m for Belgian participants and 156 (25.5) m for Vietnamese participants. The mean (SD) 6MWT distances were 625 (90.7) m for Belgian participants and 449 (70.4) m for Vietnamese participants. The Pearson correlation coefficient between the 2 tests was 0.901 (p < 0.001) for Belgian participants and 0.871 (p < 0.001) for Vietnamese participants. Age and sex were the 2 most important predictors of walking distance, followed by body mass index for Belgium and height for Vietnam. The adjusted R² ranged from 0.31 to 0.49 across 4 predictive equations. Conclusion: These results can be used to determine the presence of walking performance deficits and to guide future studies. The 2MWT is suggested as a useful and convenient alternative to the 6MWT for assessing walking performance in clinical practice.